ANALYSIS OF PUBLIC PERCEPTION TOWARDS UNSUSTAINABLE HOUSING LIVING IN PANTON REU DISTRICT, WEST ACEH REGENCY - Reyza; Anwar; Kasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine public perceptions of uninhabitable housing in Panton Reu District, West Aceh Regency. The research problem is: "What is the public perception of uninhabitable housing in Panton Reu District, West Aceh Regency?" This qualitative study, conducted by the sub-district, considers the equal status of those with decent housing and those with uninhabitable housing. Data collection was conducted through interviews and observations of eight households with uninhabitable housing. Descriptive qualitative data analysis revealed that the Panton Reu community has both positive and negative perceptions. Positive perceptions include considering the economic situation of residents of uninhabitable housing as a fate that must be accepted and appreciated due to their income. Another positive perception is the hope that residents of uninhabitable housing can build better housing with government and non-government assistance. Negative perceptions, on the other hand, focus more on social treatment, which devalues residents of uninhabitable housing, thus alienating them from their social environment. Interviews with eight households revealed that not only the physical aspects of housing were impacted, but also residents' self-confidence and social participation in community activities. Some residents of RTLH (household housing) tend to limit their social interactions due to discomfort with their living conditions. On the other hand, some members of the community show concern through moral support and encouragement for RTLH residents to receive assistance with home repairs.